Treatment-seeking behavior and barriers to mental health service utilization for depressive symptoms and hazardous drinking: The role of religious and traditional healers in mental healthcare of Northwest Ethiopia - Tesfa Mekonen Yimer; Gary CK Chan; Habte Belete; Leanne Hides; Janni Leung (Cambridge Prisms: Global Mental Health, 2023)
Understanding mental healthcare seeking and associated factors is essential for planning mental health services. This study aimed to assess treatment seeking and barriers to care for depressive symptoms and hazardous drinking in a community sample of Northwest Ethiopia. A cross-sectional study was conducted to screen 1,728 participants for depressive symptoms (n = 414) and hazardous drinking (n = 155). Participants were asked whether they had sought mental healthcare. We also assessed the barriers to seeking mental healthcare. Logistic regression was used to identify associated factors. Among people with depressive symptoms, 14.3%, 15.5%, and 19.6% sought treatment from healthcare settings, non-healthcare settings, or any sources, respectively. Religious places (39.5%) were the most helpful treatment sources. People with low levels of internalized stigma (adj OR = 3.00 [1.41, 6.42]) and positive attitudes towards mental illness (adj OR = 2.84 [1.33, 6.07]) were nearly threefold more likely to seek depression treatment. No participants with hazardous drinking sought treatment from healthcare settings, and only 1.3% had sought help from families/friends. Over 97% of participants with depressive symptoms and hazardous drinking reported at least one barrier to treatment-seeking from a healthcare setting. Religious and traditional healers were as important as healthcare settings for treatment-seeking.